Interview by Revista SANKOFA with Ahmed Mulay Ali Hamadi, representative of the Polisario Front in Brazil, October 5, 2022 - Cosenza, Apoena; Grabois, Igor (Sankofa (São Paulo), 2023)
Through Igor Grabois, Revista SANKOFA had the opportunity to interview the Polisario Front representative Ahmed Mulay Ali Hamadi, taking advantage of his visit to Brazil. The questions were prepared by Apoena Canuto Cosenza, and the interview was held on October 5th. The Polisario Front is a political organization founded on May 10, 1973. It fights for the liberation of Western Sahara and for international recognition of the Saharawi Arab Democratic Republic. Currently, Western Sahara is occupied by Moroccan troops, and its territory is divided into two: a free zone, where the government of the Saharawi Arab Democratic Republic organizes the life of its people, and a zone occupied by Morocco, where the population still fight for their freedom. In this interview, we seek to understand the meaning of this liberation struggle and its relevance for Africa and Latin America.